Cultivo de milho verde em sucessão ao arroz no Vale do Ribeira, SP: subsídios para adoção de zonas de manejo - Akune, Vanessa Satiko da Cunha [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The knowledge of the spatial variability of agronomic traits of culture and soil fertility in cultivated areas provides important information to rationalize the application of lime and fertilizers in the soil, helping to reduce the environmental impacts and production costs. This study aimed to determine the variability of the production of green maize in winter and soil fertility in commercial agriculture, in order to identify and delineate management zones for individualized treatment. The experiment was carried out and conducted in Kassuga Farm, located in the Registro- SP, in the harvest of 2013/2014. The sampling grid consisted of 68 points georreferencidos sampling, spread over an area of 4.97 ha. The planting of conventional hybrid corn was conducted in tillage, in succession to the rice harvest in winter, the harvest was performed in corn condition. The characteristics were; plant height, length, diameter, and productivity of unhusked and husked ear, grain yield and soil properties. The data were submitted to exploratory analysis to verify the degree of normality and the measure of correlation between soil attributes, corn productivity and percentage of coverage. The data showed that non-normal distribution were submitted to geostatistical analysis to quantify the degree of spatial dependence and prepare the spatial variability maps. The results showed no significant correlation productivity of corn on the cob with soil chemical properties; however, there were several interactions between the elements of fertility and soil texture. The spatial dependence of soil attributes queen spatial variations shows need to be. Considered in selecting the driving technique of the culture, conventional agriculture or precision. The chemical attributes MO, K and P showed spatial variability in the area, providing support for the establishment of different management zones, targeting the ...

O conhecimento da variabilidade espacial das características agronômicas da cultura e da fertilidade do solo em áreas cultivadas, proporciona importantes informações para a racionalização na aplicação dos corretivos e fertilizantes no solo, contribuindo para a redução nos impactos ambientais e custos de produção. O presente trabalho teve como objetivo determinar a variabilidade da produção da cultura do milho verde no inverno e da fertilidade do solo, em área agrícola comercial, com a finalidade de identificar e delimitar zonas de manejo para tratamento individualizado. O experimento foi instalado e conduzido na Fazenda Kassuga, localizada no município de Registro - SP, na safra de 2013/2014. A grade amostral foi constituída de 68 pontos de amostragem georreferencidos, distribuídos numa área de 4,97 ha. O plantio do milho híbrido convencional foi realizado em sistema de semeadura direta, em sucessão a colheita do arroz no inverno, a colheita foi realizada na condição de milho verde. As características avaliadas foram; altura das plantas, comprimento, diâmetro, e produtividade das espigas empalhadas e despalhadas, produtividade de grãos e os atributos do solo. Os dados foram submetidos a análise exploratória para verificar grau de normalidade e a medida de correlação entre os atributos do solo, produtividade do milho e porcentagem de cobertura. Os dados que apresentaram distribuição não normal, foram submetidos à análise geoestatística a fim de quantificar o grau de dependência espacial e elaborar os mapas de variabilidade espacial. Os resultados demonstraram que não houve correlação significativa da produtividade da espiga de milho verde com os atributos químicos do solo, contudo, ocorreram diversas interações entre os elementos de fertilidade e textura do solo. A dependência espacial dos atributos do solo demonstra que as variações espaciais ...
Green corn culture in succession to rice in the ribeira valley, sp: subsidies for adoption of management zones
Keywords: Mecanização agrícola; Solos - Manejo; Milho - Cultivo; Farm mechanization